Analysis of velocity- and power-load relationships of the free-weight back-squat and hexagonal bar deadlift exercises - Gantois, Petrus; de Souza Fonseca, Fabiano; Nakamura, Fábio Yuzo; de Sousa Fortes, Leonardo; Fernandez-Fernandez, Jaime; Ricarte Batista, Gilmário (Biology of Sport, 2023)
The aim of this study was to analyse the load-velocity and load-power relationships in the freeweight back-squat (BSQ) and hexagonal bar deadlift (HBD) exercises. Twenty-five (n = 25) resistance-trained men (age = 23.7±2.8 years) performed a progressive load test at maximal intended velocity to determine their BSQ and HBD one-repetition maximum (1RM). Mean propulsive velocity (MPV) during the concentric phase of the lift was recorded through a linear encoder. Load-velocity and load-power relationships were analysed by fitting linear regression and the second-order polynomial, respectively, to the data. Maximum strength (1RM), MPV (30–80% 1RM), and power output (30–90% 1RM) were higher for HBD compared to BSQ exercise (p < 0.05). A very strong relationship between MPV and relative intensity was found for both BSQ (R2 = 0.963) and HBD (R2 = 0.967) exercises. The load that maximizes power output (Pmax) was 64.6±2.9% (BSQ) and 59.6±1.1% (HBD) 1RM. There was a range of loads at which power output was not different than Pmax (BSQ: 40–80% 1RM; HBD: 50–70% 1RM). In conclusion, the load-velocity and load-power relationships might assist strength and conditioning coaches to monitor and prescribe exercise intensity in the BSQ and HBD exercises using the velocity based training approach.